Dissemination of a long‐term care planning tool, PlanYourLifespan.org, through community‐based stakeholder leaders. Issue 11 (21st July 2022) - Lindquist, Lee A.; Wong, Norine; Forcucci, Chris; Rogers, Beverly; Ramirez, Ana; Ramirez‐Zohfeld, Vanessa
Abstract: Background: Geriatrics research generally cumulates in academic journal publications, with variable diffusion to patients and communities. PlanYourLifespan.org is a free, evidence‐based tool that assists older adults, and their loved ones, to better understand and plan for their long‐term support needs. There is a need to effectively disseminate geriatrics research, such as PlanYourLifespan.org, to communities that may directly benefit from this research. Objective: To leverage community‐based stakeholder leaders, utilizing a train‐the‐trainer program, to disseminate PlanYourLifespan.org and evaluate the extent of the dissemination. Methods: Using a train‐the‐trainer strategy, community stakeholder leaders from the original study paired up with newly recruited community stakeholder leaders. New community stakeholder leaders were trained on dissemination, using a "how‐to‐disseminate" web‐based toolkit—developed as part of this project. Newly trained community stakeholder leaders subsequently trained additional community stakeholder leaders who conducted and tracked dissemination activities in their communities. Google Analytics tracked newly created PlanYourLifespan.org accounts, login sessions, and daily website visitors. Results: Five newly trained community stakeholder leaders disseminated PlanYourLifespan.org over a three‐month period. Cumulatively, on the day of the dissemination activity, there were 11, 361 PlanYourLifespan.org log‐ins (average: 378.7 log‐ins/activity day), 89, 068 log‐ins (average: 2969 log‐ins/activity week) one‐week after the activity, and 319, 154 log‐ins (average: 10, 638 log‐ins/activity month) one month after the dissemination activity. Approximately 9.4 new PlanYourLifespan.org accounts were created one‐week post dissemination activity and over 1100 new accounts in the one‐month period thereafter. Conclusions: Wide dissemination of PlanYourLifespan.org occurred by leveraging a train‐the‐trainer approach with community stakeholder leaders. Researchers should consider collaborating early on with community stakeholders to meaningfully disseminate results.